The Asymmetry of the Cosmic Microwave Background Radiation as Signature of Local Lorentz Invariance Violation - Albertini, Gianni; Cardone, Fabio; Bellucci, Stefano (Advances in High Energy Physics, 2022)
A difference in electric potential in a static conductor inside a static magnetic field and an anisotropic and asymmetric distribution of neutrons emitted in nuclear reactions induced by ultrasound are assumed as marks of local Lorentz invariance (LLI) violation. The asymmetry of the two experiments is related to the asymmetry of the Cosmic Microwave Background Radiation (CMBR). As common directions of asymmetry are found in these three cases, a fundamental asymmetry of the interactions is suggested which can also shed new light on the question of symmetry breaking in the history of the Universe.